Medieval London : Collected Papers of Caroline M. Barron - Barron, Caroline M. (Book collections on Project MUSE., 2017)
"Caroline Barron is the foremost scholar of medieval London and she has made her impact through a series of major articles revised and updated here"--Provided by publisher.